POWER DOMINATION NUMBER PADA GRAF LINTASAN COMB SISI GRAF BUKU SEGITIGA DIKAITKAN DENGAN KETERAMPILAN BERPIKIR TINGKAT TINGGI - Bawono, Darian Aji; dafik, dafik; fatahillah, arief (Department of Mathematics Education , University of Jember, 2015)
Abstract.Power dominating set is a concept of determining a minimum vertex in a graph that can dominate vertex connected around.The smallest cardinality of the power dominating set is called power domination number.Power domination number denote γp is theminimum cardinality of a power dominating set, it haswhere (G) is the power domination number of G, Z(G) is zero forching number of G,and ∆(G) is maximum degree of G. This paper is writtento fine the value of powerdomination number on graph. The used graph is pathedge comb triangular book graph. And in each phase of finding this problem is associated with high order thinking skill. Keywords:Power Domination Number,Edge Comb Product, High Order Thinking Skill